Liberarisasi Jasa Telekomunikasi Indonesia, Masuknya FDI dan Penyerapan Tenaga Kerja Domestik - Fawaiq, Muhammad (Badan kebijakan Fiskal, 2017)
AbstractThe research’s purposes is to analyze Causality between FDI in telecommunication service sector and the empolyment in that sector. The method used are the descriptive and the linear regression through PVECM estimation. The results showed that the FDI in telecommunication service sector in the period of 2000-2016, only concentrated in Java and Bali with an average contribution of 98 percent per year. The PVECM estimation showed that the FDI has a strong two-way relationship with the employment. This means that FDI significantly encourages labor and vice versa. The ECT coefficient showed that the change in FDI due to changes in employment to achieve equilibrium is 89 percent and the change of employment due to changes in FDI by 10 percent per year. Thus, the FDI provides benefits for the employment absorption and the availability of emploment is also an important consideration for investors to invest in Indonesia's telecommunications sector.